Randić decomposition of catacondensed systems - Rada, Juan (Utilitas Mathematica, 2005)
The Randić index of a simple graph G, denoted by χ, is defined as χ(G) = Σ1≤i≤j≤n-1 mij(G)/√ij where mij (G) is the number of edges in G connecting a vertex of degree i with a vertex of degree j. In this article we present a decomposition of C h, the set of catacondensed systems with h hexagons, which contains complete information on the order relation induced by χ over Ch. In particular, the extremal χ-values of important subsets of Ch are determined.